Knowledge, attitudes and practices of university adolescents about syphilis: a cross-sectional study in the Northeast - Carvalho, Rodolfo Xavier da Costa; Araújo, Telma Maria Evangelista de (Revista de Saúde Pública, 2020)
OBJECTIVE: To analyze knowledge, attitudes and practices of university adolescents about syphilis. METHODS: Cross-sectional, analytical, census-type study, developed with the universe of adolescents aged 18 and 19 years (n = 598), enrolled in three institutions of higher education in a municipality of Piauí (n = 598), which total 20 courses in the areas of Health Sciences, Applied Social Sciences, Exact and Earth, Engineering and Linguistics, Letters and Art. Data collection occurred from March to May 2019, based on a questionnaire adapted from the Pesquisa de Conhecimentos, Atitudes e Práticas da População Brasileira of 2013 (PCAP – Survey of Knowledge, Attitudes and Practices in the Brazilian Population), consisting of questions related to sociodemographic variables (gender, family arrangement, father’s schooling, mother’s schooling, skin color or race, employment, household income), knowledge, attitude and practice regarding the disease, the last three being classified by scores. The variables that presented p ≤ 0.20 in the bivariate analysis, by Pearson’s chi-square test, were included in three multivariate logistic models, and the outcomes in each model were knowledge, attitude and practice, respectively; remaining at the end those at the level of p < 0.05. RESULTS: Boys have a 39.6% lower chance of having adequate/regular knowledge (ORa = 0.604; 95%CI 0.415–0.878), whereas the highest chances are associated with “living alone, with relatives and friends” (ORa = 4.567; 95%CI 1.417–14.719) and having a very positive/positive attitude (ORa = 6.937; 95%CI 4.562–10.550). Lower chances of an adequate practice are associated with boys (ORa = 0.480; 95%CI 0.301–0.766) and lower father’s schooling (ORa = 0.440; 95%CI 0.241–0.806). CONCLUSION: Most participants’ knowledge and attitude regarding syphilis were not sufficient to the adoption of an adequate sexual practice for the prevention of the disease, showing the need to investigate other variables that may be implicated in this cognitive incoherence.